Opposing Influences of Optic Neuritis and Transverse Myelitis on the Future Location of Relapses in MOG Antibody–Associated Disease - Daniel Lordelo San Martin; Marcos Baruch Portela Filho; Chiara Rocchi; Shahd Hamid; Saif Huda (Brain and Behavior)
ABSTRACT Background Studies in MS and NMOSD have shown that relapses can frequently occur in the same location as the first attack. Factors associated with this outcome in MOGAD are unclear. Objective The objective of this study was to investigate the likelihood of a relapse occurring at the same site in MOGAD. Methods This was a UK national cohort study. MOGAD patients with a minimum of one relapse and one year of follow‐up were included. To identify factors associated with relapse location, logistic regression was performed. Results An increased risk of a relapse in the same location was observed when the first attack was optic neuritis—for the second attack (OR 12.9, 95% CI 3.31–50.55, p = .001) and all subsequent attacks (OR 5.39 95% CI 1.61–18.03, p = .006). Conversely, a reduced risk of relapse in the same location was associated with transverse myelitis—for the second attack (OR 0.25, 95% CI 0.07–0.82, p = .022) and all subsequent attacks (OR 0.25 95% CI 0.06–0.96, p = .045). Conclusion In relapsing MOGAD, patients with optic neuritis are at high risk of a new attack in the same location, while those with transverse myelitis are at low risk.